EFFECT OF COMPOUND FERTILIZER AND FOLIAR APPLICATION OF IRON , GIBBERELLIC ACID ON THE GROWTH AND YIELD OF SALEMY POMEGRANATE CULTIVAR (Punica granatum L.) 1. SETTING , GROWTH AND SOME FRUIT CHARACTERISTICS - Nabil M. Ameen Al-Imam (Mesopotamia Journal of Agriculture)
This investigation had been conducted in an special orchard in Al-Hawija town which belongs to Kirkuk governorate for two growing seasons during 2005 and 2006 in order to study the effect of NPK fertilizer and foliar application of iron and gibberellic acid (GA3) and their interactions on the setting , growth and some fruit characteristics of Pomegranate (Punica granatum L.) trees CV. Salemy . The trees fertilized by compound fertilizer (NPK) at rates of 0 , 440 and 880 Kg/Hectare , and the trees were sprayed by iron (Fe–HEEDA) at rates of 0 , 100 and 200 mg Fe/l and gibberellic acid (GA3) was at rates of 0 , 100 and 200 mg GA3/l . The results showed that NPK fertilizer, Iron and gibberellic acid sprayed caused non-significant differences at the flowering, fruit abscission and fruit setting characteristics . There are significant increment in leaves chlorophyll contents, leaf area, flesh percentage of fruit, thickness and weight of epicarps when 880 kg NPK/Hectare fertilizer or 200 mg Fe/l or 200 mg GA3/l were used alone. Interaction between 880 kg NPK/Hectare + 200 mg Fe/l + 200 mg GA3/l gave the best result for the chlorophyll content and the leaf area for both seasons .